Computer-aided complete blood counts in dairy cattle of the Thessaloniki region: A clinical study - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z.; FORTOMARIS (Π. ΦΟΡΤΟΜΑΡΗΣ) P.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ) A.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study reports the findings of complete blood counts (CBC), performed in 100 Friesian dairy cattle of various cattle farms in the Thessaloniki region. Farm selection was done with the criteria of proper management standards, such as housing, feeding schedules, vaccinations and deworming. According to their age and reproductive status, the animals were allocated in following five groups: • Group I: calves 0-3 months old. • Group II: calves 3-14 months old. • Group III: cows 14 months-3 years old. • Group IV: cows older than 3 years. • Group V: cows in the dry period. Analysis included the determination of hematocrit, hemoglobin, leucocyte and platelet counts with the aid of the veterinary hematology analyzer IDEXX QBC®, using the procedure specifically proposed for this animal species. Differential leucocyte counts were also done from blood smears prepared from each sample. Mean values of all the parameters evaluated were within the normal limits, reported in the literature.